Circuit model of microstrip patch antenna on ceramic land grid array package for antenna-chip codesign of highly integrated RF transceivers - Wang, Jun Jun (2009)
This paper presents the circuit model of a microstrip patch antenna on a ceramic land grid array (CLGA) package for the antenna-chip codesign of a highly integrated radio-frequency (RF) transceiver. The microstrip patch antenna is fed by packaging interconnect components such as bond wires, signal traces, and vias in a ground-signal-ground (G-S-G) configuration from the